Persepsi Sosial Generasi Milenial di Saat Penerapan Adaptasi Kebiasaan Baru di Sulawesi Utara: Millennials' Social Perceptions When Implementing New Habit Adaptations in North Sulawesi - Nikolas Fajar Wuryaningrat; Deitje Adolfien Katuuk; Lydia Ivana Kumajas; Ignatius Javier Couturier Tuerah (Society, 2021)
In the current era of adapting new habits (abbreviated as Adaptasi Kebiasaan Baru or AKB), it is an opportunity for the millennial generation to get out of their ‘cage’ and do activities outside the home. This study aims to describe the perception of the millennial generation on the application of adopting new habits during the COVID-19 pandemic. This research was conducted using a survey research method with descriptive analysis techniques to obtain this description. In this research, millennials are represented by state university students in North Sulawesi Province. The sample of this study was 400 active student respondents. The data was collected through research instruments sent online with the Google Forms application. The study results indicate that millennials are worried when implementing new habit adaptations when they are active outside the home. The research results also show that the first thing they want to do is go to a house of worship. Millennials in North Sulawesi also perceive an excellent level of trust in local and central governments in dealing with the COVID-19 pandemic. It can be concluded that millennials in North Sulawesi are optimistic about their future sustainability.